Professional outcomes and psychological health after workplace bullying: an exploratory follow-up study - Fiabane, Elena; Flachi, Daniela; Giorgi, Ines; Crepaldi, Ilaria; Candura, Stefano M.; Mazzacane, Fulvio; Argentero, Piergiorgio (La Medicina del Lavoro, 2015)
Background: The literature shows that workplace bullying can lead to negative consequences for both individuals’ health and professional outcomes. Most of these studies used cross-sectional designs and self-report questionnaires and further research is needed in order to explore long-term effects of workplace bullying. Objectives: This follow-up study aimed to explore professional and psychological outcomes in a sample of subjects who required a specialized and multidisciplinary assessment for psychological problems related, in their opinion, to workplace bullying. Methods: The sample includes 71 patients with a baseline diagnosis of work-related psychological disorder who were assessed at follow-up by means of a structured telephone interview. The interview included structured questions about professional career developments and psycho-somatic health, and administration of the General Health Questionnaire-12. Results: 62.0% of the participants were currently working and, of these, 59.1% had changed workplace after experiencing mobbing. Patients who changed workplace scored significantly higher on job satisfaction levels (p<0.01) and showed lower levels of social dysfunction (p<0.01) compared to those who did not change their job. Patients with a baseline diagnosis of Adjustment disorder/Post-Traumatic Stress disorder had higher levels of general dysphoria (p<0.04) and social dysfunction (p<0.01) at follow-up than other patients. Conclusions: These findings stress the importance of an accurate diagnostic assessment of mobbing-related psychopathological disorder. Victims of workplace bullying require early and continuous psychological support in order to promote their psychological well-being and work reinstatement.